Healthcare-seeking experiences of older citizens in Bangladesh: A qualitative study. - Abdur Razzaque Sarker; Irfat Zabeen; Moriam Khanam; Ruckshana Akter; Nausad Ali (Public Library of Science (PLoS), 2023)
Despite improvements in many health indicators in the last few decades, providing access to affordable and quality healthcare for older citizen remains a considerable challenge in Bangladesh. This study aimed to understand individuals 'experiences regarding their healthcare-seeking, treatment cost, accessibility and coping mechanisms for the promotion of appropriate strategies to enhance the quality of life of the older citizens of Bangladesh.A qualitative descriptive approach was used in this study. A total of 27 In-Depth Interviews (IDIs) were conducted in a district in Bangladesh with older people between January and February 2020, where gender distribution was equal. Face-to-face interviews were conducted by trained and experienced interviewers regarding healthcare-seeking and accessibility, affordability, and healthcare coping strategy. Thematic analysis was conducted to analyse the data. It was found that the health condition of the older population is not satisfactory. Most of them had been suffering from several diseases such as benign tumor, chronic kidney disease, body aches, gastric ulcers for a longer period of time. The majority of the participants were suffering from multiple non-communicable diseases while diabetes and hypertension were the foremost of all diseases. This study provides insight into the challenges of managing healthcare services for older citizens in Bangladesh. Healthcare facilities were available, but high out-of-pocket payments, lack of caregivers, and time distance created a barrier to the service provision. The findings indicated that geriatric care policymakers and service providers should prioritize the older-friendly health infrastructures with affordable cost of treatment for the betterment of the health status of older citizens in Bangladesh.